IMPORTANCE OF AAA SIZE AS A PREDICTOR OF COMPLICATIONS AFTER EVAR - Oliveira-Pinto, José (2020)
Introduction: EVAR represents the preferred modality for Abdominal Aortic Aneurysms (AAA) repair. However, a comprehension regarding its limits is paramount to avoid future complications. AAA sac diameter has been described as a relevant risk factor for late complications. The purpose of this study is to summarize relevant findings regarding the association between AAA diameter and AAA-related complications. Methods: MEDLINE databases were searched to identify data addressing specific information on the relation between AAA sac diameter and incidence of AAA-related complications. Only articles in English language between 2003 and 2019 was included. Primary endpoint was freedom from aneurysm-related complications. Results: Five studies were included in our report, including 8443 patients. In two of the included studies patients with larger AAA sacs were at increased risk for aneurysm-related complications after EVAR (HR 1.02 per mm increase CI95% 1.01–1.04 and HR 1.8 95% CI, 1.20–2.72; P = .005). Two studies reported a higher risk of post implant ruptures (HR: 7.7 CI95% 3.1–18.7;) and late conversions (HR 1.6 CI 95% 1.1–2.3) in patients with AAA diameters over 6 and 6.5 cm, respectively. Finally, one study reported a higher rate of neck-related events in patients with AAA diameter > 65mm [HR: 6.4 (2.3–17.7)]. Conclusion: AAA diameter is a relevant risk factor for late complications. However, research is needed to clarify is these are attributable to the challenging associated anatomy or to the space free of thrombus within the sac. Judicious technique choice along with tailored follow-up strategies are advised in this subgroup of patients.